C47 CORO–CT PLAQUE ANALYSIS IN ASSESSMENT OF CARDIOVASCULAR RISK. (18th May 2022) - Montonati, C; Pergola, V; Dellino, C; Continisio, S; Mattesi, G; Zolin, A; Scarpa, F; Storer, V; Gentili, A; Cabrelle, G; Cattarin, S; Motta, R; et al.
Abstract: Background: Computed tomographic (CT) coronary angiography represents a non–invasive approach to assess plaque characteristics that provides information to change treatment of coronary artery disease (CAD) and to asses risk stratification. Purpose: Analyze the differences in plaque composition between patients with different plaque features: soft unstable plaques, hard stable plaques and no plaques; identify whether there is a relationship between the plaque density and the pericoronary fat attenuation index (pFAI). Materials and methods: 372 patients retrospectively analyzed who underwent CTCA for exclusion of CAD. They were divided into three groups: 37 (10%) patients with high attenuated plaques (> 60HU), 137 (37%)with low attenuated plaques (<29 HU and a volume of at least 15 mm3 and/or 30–59 HU with a volume greater than 52 mm3) and 198 (53%) patients without significant CAD. For each patients we collected clinical, radiological and follow–up data. Results and Discussion: Low–attenuated plaques are significantly associated with older age, male sex, dyslipidemia and diabetes mellitus (p < 0.001). Higher values of pFAI were more present in patients with soft plaques than in those with stable plaques and without plaques (p = 0.005). It was also found that soft plaques were present in more CA segments compared to stable plaques. Overall volume of soft plaque appears greater than hard plaques and mainly localized in the anterior descendant coronary artery with higher stenosis values (p < 0.001). Presence of plaques with soft or high–risk features predisposes significantly and independently (p < 0.001) to a composite outcome (death, in–hospital admissions for percutaneous angioplasty or by–pass procedures) at the follow up. Conclusions: Coronary plaque analysis showed a good correlation between high–risk plaques and pFAI, supporting the hypothesis that the presence of high–risk plaques can be correlated to inflammatory burden. Furthermore, the presence of high risk plaques predispose to death or hospitalization for coronary intervention.